Orientasi Wirausaha dan Network Capability dalam Upaya Peningkatan Kinerja pada IKM Penyamakan Kulit di Sukaregang Kabupaten Garut - Fitrin Rawati; Husni Muharam; Erik Kartiko (Fakultas Ekonomi Universitas Garut, 2019)
The purpose of this study was to determine the effectiveness of entrepreneurial orientation and network capability on the performance of the leather tanning IKM in Sukaregang, Garut Regency, and to determine the supporting and inhibiting factors of entrepreneurial orientation and network capability at the leather tanning IKM in Sukaregang, Garut Regency. As for the research method, for descriptive data analysis with frequency analysis and verification analysis with the help of software Partial Least Square (PLS) version 3.0. The finding of this research is that entrepreneurial orientation is effective in improving the performance of the leather tanning IKM in Sukaregang, Garut Regency. Then Network capability is effective in improving the performance of the leather tanning IKM in Sukaregang, Garut Regency. The supporting factor for entrepreneurial orientation is the Level of Commitment to Company Resources, while the inhibiting factor for entrepreneurial orientation at the leather tanning IKM in Sukaregang, Garut Regency is the Level of Courage to Invest with Uncertain Returns. Then the supporting factor for network capability at the leather tanning IKM in Sukaregang, Garut Regency is the ability to build good personal relationships with business partners. Meanwhile, the inhibiting factor for network capability at the leather tanning IKM in Sukaregang, Garut Regency is the level of knowledge of partner strengths.